PIN2 is required for the adaptation of Arabidopsis roots to alkaline stress by modulating proton secretion - Xu, Weifeng (Oxford University Press, 2012)
Soil alkalinity is a widespread environmental problem that limits agricultural productivity. The hypothesis that an auxin-regulated proton secretion by plasma membrane H(+)-ATPase plays an important role in root adaption to alkaline stress was studied. It was found that alkaline stress increased auxin transport and PIN2 (an auxin efflux transporter) abundance in the root tip of wild-type Arabidopsis plants (WT). Compared with WT roots, the pin2 mutant roots exhibited much reduced plasma membrane H(+)-ATPase activity, root elongation, auxin transport, and proton secretion under alkaline stress. More importantly, roots of the pks5 mutant (PKS5, a protein kinase) lacking PIN2 (a pks5/pin2 double mutant) lost the previous higher proton-secretion capacity and higher elongation rate of primary roots under alkaline stress. By using Arabidopsis natural accessions with a high proton-secretion capacity, it was found that their PIN2 transcription abundance is positively related to the elongation rate of the primary root and proton-secretion capacity under alkaline stress. Taken together, our results confirm that PIN2 is involved in the PKS5-mediated signalling cascade under alkaline-stress and suggest that PIN2 is required for the adaptation of roots to alkaline stress by modulating proton secretion in the root tip to maintain primary root elongation.